Optimization of distribution and transportation systems using distribution requirement planning method and greedy algorithm - Nova Audry Utami; R. Maisaroh Rezyekiyah Siregar (Desimal: Jurnal Matematika, 2025)
Effective distribution and transportation systems are crucial for enhancing a company's competitive advantage and productivity. This research evaluates the application of the Distribution Requirements Planning method and a greedy algorithm to improve the distribution of crude palm oil at PT. Agrojaya Perdana. DRP is used to project distribution needs using a quantitative approach based on historical demand data. The research results demonstrate that the integration of Distribution Requirement Planning Method and the greedy algorithm is effective in increasing distribution efficiency, reducing delivery times, and optimizing distribution scheduling. Calculations using the integrated Distribution Requirements Planning method show that PT. Argojaya will supply 12,501 tons of Crude Palm Kernel Oil from May to October 2025. Furthermore, the greedy algorithm minimizes routes for each company and prioritizes shipments to PT. Musim Mas, resulting in a profit of IDR 17,851,743,750.